The luminal Ca(2+) chelator, TPEN, inhibits NAADP-induced Ca(2+) release. - Morgan, A; Parrington, J; Galione, A (2012)
The regulation of Ca(2+) release by luminal Ca(2+) has been well studied for the ryanodine and IP(3) receptors but has been less clear for the NAADP-regulated channel. In view of conflicting reports, we have re-examined the issue by manipulating luminal Ca(2+) with the membrane-permeant, low affinity Ca(2+) buffer, TPEN, and monitoring NAADP-induced Ca(2+) release in sea urchin egg homogenate. NAADP-induced Ca(2+) release was almost entirely blocked by TPEN (IC(50) 17-25μM) which suppressed the maximal extent of Ca(2+) release without altering NAADP sensitivity. In contrast, Ca(2+) release via IP(3) receptors was 3- to 30-fold less sensitive to TPEN whereas that evoked by ionomycin was essentially unaffected. The effect of TPEN on NAADP-induced Ca(2+) release was not due to an increase in the luminal pH or chelation of trace metals since it could not be mimicked by NH(4)Cl or phenanthroline. The fact that TPEN had no effect upon ionophore-induced Ca(2+) release also argued against a substantial reduction in the driving force for Ca(2+) efflux. We propose that, in the sea urchin egg, luminal Ca(2+) is important for gating native NAADP-regulated two-pore channels.